Healthcare and unhealthy eating among children aged under two years: data from the National Health Survey, Brazil, 2013 - Patricia Constante Jaime; Paulo Germano de Frias; Helena Oliveira da Cruz Monteiro; Paulo Vicente Bonilha Almeida; Deborah Carvalho Malta
Abstract Objectives: to examine indicators relating to access to child health care and markers of unhealthy patterns of eating in Brazilian children aged under two years and to set these in the context of the National Health System 's current child healthcare agenda. Methods: a descriptive cross-sectional study using data from the 2013 National Health Survey. Prevalences and confidence intervals of 95% (CI95%) were estimated for the total population, Brazilian macroregions and urban or rural location of household. Results: a first medical consult before the seventh day of life was reported in only 28.7% of children. Supervision of growth and child development was carried out primarily at basic health units (57.2%; CI95%: 54.8-59.6). Theneonatal screening, newborn hearing screening and red reflex tests were conducted with a frequency of 70.8% (CI95%: 69.0-72.7), 56.0% (CI95%: 53.8-58.3) and 51.1% (CI95%: 48.9-53.3), respectively. Disparities were found in preventive health care, with lower access among children living in rural households or in the North and Northeast regions. Soda consumption was reported for 32.3% and consumption of biscuits or cake for 60.8% of children,indicating premature introduction of unhealthy foods into the child's diet. Conclusions: the findingspoint to disparities in access to child healthcare and a high prevalence of unhealthy eating habits in infancy.